Carcinoma renal dos ductos de Bellini - Helio Begliomini (Revista do Colégio Brasileiro de Cirurgiões)
Two types primary epithelial tumours of the kidney have been distinguished, such as renal cell carcinoma (hypernephroma or Grawitz) deriving from proximal tubules and carcinoma arising in the urothelium of the kidney's collecting system. Mancilla-Jimenez e cols were the first to describe in 1976 an atypical papillary carcinoma of the kidney deriving from collecting duct system-Bellini duct carcinoma (BDC). In the World Healthy Organization classification it is listed as a rare carcinoma ( 1 % of the renal malignancies) originating in the renal medulla. Histologic examination shows both tubular and papillary architeture, which can lead to misinterpretation as renal cell or transitional cell carcinoma. Renal cell carcinoma originates from the metanephrogenic blastema and collecting duct carcinoma derived embryologicaly from the mesonephron Wolff duct. Renal cell carcinoma has been shown to express both cytokeratins and vimetin, whereas the distal convoluted tubule expresses only cytokeratins. BDC can be considered as a renal malignancy with a very bad prognosis compared to the other renal cell carcinoma. The best treatment is radical nephrectomy. A case of BDC is reported in a young black man, 27 year old with only history of light left back pain. Ultrasound and other image examinations showed a tumour about 6 cm in the middle and low left kidney. Patient was submitted to extraperitoneal radical nephectomy. Microscopic evaluation revealed kidney's collecting duct carcinoma with metastasis on two retroperitoneal lymphy nodes.